ENHANCEMENT OF STUDENTS’ CRITICAL THINKING SKILL AND WRITING ACHIEVEMENT THROUGH GUIDED-INQUIRY LEARNING - Juansyah, Mardi; Arono, Arono; Yunita, Wisma (Universitas Muhammadiyah Metro, 2024)
While many studies have explored the enhancement of critical thinking skills through inquiry and guided inquiry learning models, there is no research specifically examining the impact of the guided inquiry learning model on both critical thinking and writing achievement in the EFL context. This study aimed to examine the potential of the Guided Inquiry Learning model to enhance critical thinking skills and English writing achievement. This study was quasi-experimental research with a pretest-posttest control group design. A cluster random sampling technique was used to get two groups of samples. One experimental group was taught by guided inquiry learning, and one control group was taught without guided inquiry learning. The data were collected through six-item essay tests to measure students' critical thinking skills and writing tests to measure students' writing achievement. Those data were analyzed descriptively and inferentially. The prerequisite test of normality and homogeneity preceded the analysis of the t-test. The results of data analysis showed: 1) there is an increased score for students' critical thinking skills and writing achievement in each group, and 2) there is a significant difference in students' critical thinking skills (with sig. value of 0.000) and students' writing achievement (with sig. value of 0.005) after the implementation of guided inquiry learning model. The findings of this research highlight the significance of incorporating the GIL model into EFL instruction to equip students' writing achievement and critical thinking skills.